Comparison of prostate cancer diagnosis in patients receiving unrelated urological and non‐urological cancer care. (25th June 2013) - Corcoran, Anthony T.; Smaldone, Marc C.; Egleston, Brian L.; Simhan, Jay; Ginzburg, Serge; Morgan, Todd M.; Walton, John; Chen, David Y.T.; Viterbo, Rosalia; Greenberg, Richard E.; Uzzo, Robert G.; Kutikov, Alexander
<x xml:space="preserve">Abstract</x> Objective To evaluate prostate cancer diagnosis rates and survival outcomes in patients receiving unrelated (non‐prostate) urological care with those in patients receiving non‐urological care. Materials and Methods We conducted a population‐based study using the Surveillance Epidemiology and End Results (SEER) database to identify men who underwent surgical treatment of renal cell carcinoma (RCC; n = 18 188) and colorectal carcinoma (CRC; n = 45 093) between 1992 and 2008. Using SEER*stat software to estimate standardized incidence ratios (SIRs), we investigated rates of prostate cancer diagnosis in patients with RCC and patients with CRC. Adjusting for patient age, race and year of diagnosis on multivariate analysis, we used Cox and Fine and Gray proportional hazards regressions to evaluate overall and disease‐specific survival endpoints. Results The observed incidence of prostate cancer was higher in both the patients with RCC and those with CRC: SIR = 1.36 (95% confidence interval [CI] 1.27–1.46) vs 1.06 (95% CI 1.02–1.11). Adjusted prostate cancer SIRs were 30% higher (P < 0.001) in patients with RCC. Overall (hazard ratio = 1.13, P < 0.001) and primary cancer‐adjusted mortalities (sub‐distribution Hazard Ratio (sHR) = 1.17, P < 0.001) were higher in patients with RCC with no significant difference in prostate cancer‐specific mortality (sHR = 0.827, P = 0.391). Conclusion Rates of prostate cancer diagnosis were higher in patients with RCC (a cohort with unrelated urological cancer care) than in those with CRC. Despite higher overall mortality in patients with RCC, prostate cancer‐specific survival was similar in both groups. Opportunities may exist to better target prostate cancer screening in patients who receive non‐prostate‐related urological care. Furthermore, urologists should not feel obligated to perform prostate‐specific antigen screening for all patients receiving non‐prostate‐related urological care.